Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1111/j.1095-8649.2010.02609.x
|View full text |Cite
|
Sign up to set email alerts
|

Panbiogeographical analysis of the shark genus Rhizoprionodon (Chondrichthyes, Carcharhiniformes, Carcharhinidae)

Abstract: The distributional patterns of the seven species of Rhizoprionodon were analysed using the panbiogeographical method of track analysis. The individual tracks of Rhizoprionodon suggest that the genus is mainly an Indian-Atlantic Ocean group. Five generalized tracks were found: (1) Caribbean, defined by R. porosus and R. terraenovae; (2) eastern coast of South America, defined by R. porosus and R. lalandei; (3) Indian Ocean, defined by R. acutus and R. oligolinx; (4) north-western Australia, defined by R. acutus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…This is counter-intuitive to the process of allopatric speciation, driven by vicariant events, that is thought to have shaped the evolutionary history of the majority of marine organisms. In reality, it is the imprint of marine vicariant events, such as the collision of the African and Asian continents in the Miocene (23 to five million years ago) that shaped the evolution of species within the genus Rhizoprionodon (Gallo et al 2010), as well as marine dispersal processes that drive marine species diversity (Barber and Bellwood 2005;Bourjea et al 2007;Schluessel et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is counter-intuitive to the process of allopatric speciation, driven by vicariant events, that is thought to have shaped the evolutionary history of the majority of marine organisms. In reality, it is the imprint of marine vicariant events, such as the collision of the African and Asian continents in the Miocene (23 to five million years ago) that shaped the evolution of species within the genus Rhizoprionodon (Gallo et al 2010), as well as marine dispersal processes that drive marine species diversity (Barber and Bellwood 2005;Bourjea et al 2007;Schluessel et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Sphyrna lewini is a coastal and semi-oceanic shark found worldwide in the Atlantic, Pacific and Indian Oceans (Baum et al 2007). Rhizoprionodon acutus is a continental shelf species with a more restricted distribution on the western and eastern African coasts, in the Arabian Sea, the Indo-West Pacific Ocean and the northern Australian coastline (Gallo et al 2010). There is a considerable size difference between the species: S. lewini is large with a maximum size of around 340 cm (TL) and R. acutus is much smaller (100 cm, Australia; 178 cm, Africa) (Last and Stevens 2009).…”
Section: Introductionmentioning
confidence: 99%
“…First recorded in the Early Eocene of Morocco (Arambourg, 1952), Cenozoic evidence of the genus Rhizoprionodon is relatively common in tropical deposits of the Tethys seaway during the Late Eocene, from the Caribbean sea to the Jordanian coast (e.g., Case, 1981;Mustafa and Zalmout, 2002), leading some authors to propose that the current distribution of the seven recent species, today unknown in Mediterranean sea, is most likely a result of a former widespread distribution along Tethyan mangroves in the mid-Cenozoic, affected by successive vicariance events (Briggs, 1995;Musik et al, 2004;Gallo et al, 2010). It is noteworthy that certain extant species of Rhizoprionodon are possibly known since Late Eocene deposits but distinctive specific characters on teeth suffer from a conservative dental morphology among genera, as observable in the literature devoted to those taxa (Springer, 1964;Compagno, 1988;Herman et al, 1991).…”
Section: Remarksmentioning
confidence: 99%
“…It is interesting to note that the problem of finding generalized tracks where only parts of individual tracks overlap has been found also in some manual analyses (e.g. Nihei & de Carvalho, 2005;Gallo et al, 2007Gallo et al, , 2010, where the number of generalized tracks found is larger than that expected (≤ n/2, where n is the number of individual tracks).…”
Section: Generalized Tracksmentioning
confidence: 88%